Kewirausahaan Di Era Digital - Yusuf Suhardi; Meita Pragiwani; Zukarnaini Zulkarnaini; Arya Darmawan; Sri Handoko Sakti (BERDAYA: Jurnal Pendidikan dan Pengabdian Kepada Masyarakat, 2023)
Lecturers at the Jakarta Indonesian College of Economics provided counseling about entrepreneurship in the context of Community Service with topics that are appropriate in the current era, namely Entrepreneurship in the Digital Era. This is an adjustment to the times. Community service using lecture and discussion methods to high school students whose content needs to be emphasized that today's business needs to master e-commerce. Because e-commerce is defined as the process of buying and selling between two parties in a company by exchanging goods, services or information via the internet. This is the world of digital entrepreneurship, namely entrepreneurship that is influenced by, or takes advantage of, digital transformation in business. In this development, millennials, including Pelita Tiga High School students, absorb digital business knowledge more easily than the older generation.